A community without history? A life story approach to Romany memory and ethnicity. Issue 1 (June 2019) - Šūpulis, Edmunds
Abstract : This paper approaches Romany memory culture through life stories and is based on results and conceptualizations from the study of biographical narratives and life experiences obtained within various ethnic and cultural settings in Latvia. It explores how the experience of living under different political regimes is conveyed in communicative memory through collected life stories of Roma people. Many studies point out the apparent indifference to history in Roma communities. Roma people do not seek to emphasize their distinct identity, and their history is not fixed in artefacts such as monuments and national narratives. Analysis of Romany life stories allows the perception of relationship between the status of a given group in society, Gypsies' historical experience, and their neglect of the past.